Terahertz quasi time-domain spectroscopy based on telecom technology for 1550 nm - Kohlhaas, Robert B.; Rehn, Arno; Nellen, Simon; Koch, Martin; Schell, Martin; Dietz, Roman J. B.; Balzer, Jan C. (Optics express, 2017)
We present a fiber-coupled terahertz quasi time-domain spectroscopy system driven by a laser with a central wavelength of 1550 nm. By using a commercially available multimode laser diode in combination with state-of-the-art continuous wave antennas, a bandwidth of more than 1.8 THz is achieved. The peak signal-to-noise ratio is around 60 dB. A simulation based on the optical spectrum of the laser diode and the transfer function of the THz path is in agreement with the experimental results. The system is used to extract the refractive index from two different samples and the results indicate that the performance is up to 1.8 THz comparable to a terahertz time-domain spectroscopy system.